Immunovirotherapy for Pediatric Solid Tumors: A Promising Treatment That is Becoming a Reality - de la Nava, Daniel; Selvi, Kadir Mert; Alonso, Marta M. (Frontiers in Immunology, 2022)
Immunotherapy has seen tremendous strides in the last decade, acquiring a prominent position at the forefront of cancer treatment since it has been proven to be efficacious for a wide variety of tumors. Nevertheless, while immunotherapy has changed the paradigm of adult tumor treatment, this progress has not yet been translated to the pediatric solid tumor population. For this reason, alternative curative therapies are urgently needed for the most aggressive pediatric tumors. In recent years, oncolytic virotherapy has consolidated as a feasible strategy for cancer treatment, not only for its tumor-specific effects and safety profile but also for its capacity to trigger an antitumor immune response. This review will summarize the current status of immunovirotherapy to treat cancer, focusing on pediatric solid malignancies. We will revisit previous basic, translational, and clinical research and discuss advances in overcoming the existing barriers and limitations to translate this promising therapeutic as an every-day cancer treatment for the pediatric and young adult populations.